The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1103/physrevb.80.054403
|View full text |Cite
|
Sign up to set email alerts
|

Finite-temperature Néel ordering of fluctuations in a plaquette orbital model

Abstract: We present a pseudo-spin model which should be experimentally accessible using solid-state devices and, being a variation on the compass model, adds to the toolbox for the protection of qubits in the area of quantum information. Using Monte Carlo methods, we find for both classical and quantum spins in two and three dimensions Ising type Néel ordering of energy fluctuations at finite temperatures without magnetic order. We also readdress the controversy concerning the stability of the ordered state in the pres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…We have shown that the local average values of these effective spins correspond with the average values of the bonds in the initial ladder so the long-range spin-spin correlations in the ground-subspace are the long-range bond-bond correlations in the Cx-Cz model. This resembles the Néel order of the plaquettes energies found in the two-dimensional plaquette orbital model [40], however it has been shown that this is an artifact of a deeper lying orientational order [41]. The polarized ground state configuration of the effective spins is slightly distorted by the quantum interaction terms that cause a two-sublattice modulation of the order such that the sublattices are related by the interchange of the x and z spin components.…”
Section: Discussionmentioning
confidence: 58%
“…We have shown that the local average values of these effective spins correspond with the average values of the bonds in the initial ladder so the long-range spin-spin correlations in the ground-subspace are the long-range bond-bond correlations in the Cx-Cz model. This resembles the Néel order of the plaquettes energies found in the two-dimensional plaquette orbital model [40], however it has been shown that this is an artifact of a deeper lying orientational order [41]. The polarized ground state configuration of the effective spins is slightly distorted by the quantum interaction terms that cause a two-sublattice modulation of the order such that the sublattices are related by the interchange of the x and z spin components.…”
Section: Discussionmentioning
confidence: 58%
“…It is not clear, though, whether this might lead to useful results for the study of this specific model. Another relevant model is the plaquette orbital model that was studied in [28,3]; interactions between neighbours x, y are of the form −S i x S i y , with i being equal to 1 or 3 depending on the edge.…”
Section: Setting and Resultsmentioning
confidence: 99%
“…Recently, an interesting variant of the orbital compass model has been proposed and studied by Wenzel and Janke [37]. Their model, which they termed the plaquette orbital model (POM), is most naturally defined over the square lattice Z 2 , although generalizations to higher dimensions are straightforward.…”
Section: The Plaquette Orbital Modelmentioning
confidence: 99%
“…In [37] Wenzel and Janke studied the POM numerically both in its classical and quantum version. For an order parameter they chose the plaquette energy,…”
Section: The Plaquette Orbital Modelmentioning
confidence: 99%